Cerebellar Abiotrophy in Nelore: First Report in Zebu Cattle (Bos taurus indicus) - Oliveira, Taismara S.; Lima, Safira R. D.; Furtini, Ronaldo; Bull, Valquiria; Costa, Érica A.; Paixão, Tatiane A.; Santos, Renato L. (Brazilian Journal of Veterinary Pathology, 2011)
Cerebellar abiotrophy (CA) is a degenerative disorder of the central nervous system (CNS) that has been reported in humans and animals. In cattle, CA had been reported in Bos taurus taurus and crossbreed cattle. CA is characterized by degeneration and loss of Purkinje cells and decrease in the population of granule cells. The pathogenesis of this process is unknown, but it is believed that there is an autosomal recessive heritable factor involved. A 15-month-old Nelore ox (Bos taurus indicus) was sent to a slaughterhouse, where it presented cerebellar ataxia, symmetrical hypermetria, spasticity, ptyalism, and incoordination. There were no macroscopic changes. CNS samples were negative for BSE, rabies, and other infectious pathogens. Microscopically, there was atrophy of the molecular, granular, and Purkinje cell layers of the cerebellar cortex, and a marked and diffuse loss of the Purkinje cells. No other microscopic lesions were observed in CNS. These findings were consistent with cerebellar abiotrophy. To the best of our knowledge, no cases of CA have ever been reported in Bos taurus indicus. Therefore, the present case of CA in Nelore is the first report of the disease in Zebu cattle.